2011
DOI: 10.1155/2011/498460
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Loss of Genome Gap Region in 4p16.3 Subtelomere in Early-Onset Type 2 Diabetes Mellitus

Abstract: A small portion of Type 2 diabetes mellitus (T2DM) is familial, but the majority occurs as sporadic disease. Although causative genes are found in some rare forms, the genetic basis for sporadic T2DM is largely unknown. We searched for a copy number abnormality in 100 early-onset Japanese T2DM patients (onset age <35 years) by whole-genome screening with a copy number variation BeadChip. Within the 1.3-Mb subtelomeric region on chromosome 4p16.3, we found copy number losses in early-onset T2DM (13 of 100 T2DM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…This contact may explain why specific subtelomeric regions preferentially associate and share a high degree of sequence identity despite mapping to nonhomologous chromosomes (Hirai et al 2005). The high sequence identity among subtelomeric regions has been an important consideration in understanding changes in the chromatin environment related to some human genomic disorders (Gerber et al 2011;Kudo et al 2011;van der Maarel et al 2011).…”
mentioning
confidence: 99%
“…This contact may explain why specific subtelomeric regions preferentially associate and share a high degree of sequence identity despite mapping to nonhomologous chromosomes (Hirai et al 2005). The high sequence identity among subtelomeric regions has been an important consideration in understanding changes in the chromatin environment related to some human genomic disorders (Gerber et al 2011;Kudo et al 2011;van der Maarel et al 2011).…”
mentioning
confidence: 99%
“…Whole-genome screening with a copy number variation by Kudo et al in T2DM patients revealed that loss of copy number within the 1.3-Mb of chromosome 4p16.3 sub-telomeric region (contains 34 putative genes)was associated with early-onset T2DM. (Kudo et al, 2011).…”
Section: Telomere and Diabetes: Genetic Perspectivementioning
confidence: 99%
“… 28 , 29 The Agilent high-density custom-made array is a high-resolution array based on the comparative genomic hybridisation method, with 60 mer probes synthesised in situ as oligonucleotide arrays, at a spacing of 100 bp to 500 bp. 8 , 17 , 30 In the present study, the CNV region analysed on 9q22.31 and its flanking region contained the coding regions of the ASPN gene and the extracellular matrix protein 2 ( ECM2 ) gene ( Figs 2 and 3 ). This region contains multiple low-copy repeats in a small region of the genome, such as the ASPN D, which account for the instability of this region and trigger a copy number loss by an unequal crossing-over or end-joining event.…”
Section: Discussionmentioning
confidence: 74%